Odontogenic sinusitis due to radix perforation into the maxillary sinus on CBCT radiograph: a case report - Gunawan, Gunawan; Fitria, Ivony; Nismal, Harfindo; Sari, Desy Purnama (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: The purpose of this article was to provide an overview and examination guide in identifying odontogenic sinusitis due to radix perforation into the maxillary sinus by dental action or iatrogenic in dentistry using the CBCT modality. Case Report: A 33-year-old female patient presented to the Radiology Installation of RSGM Andalas University with a referral for CBCT, following a diagnosis of odontogenic sinusitis. According to the patient’s medical history, she had been experiencing headache and dizziness for five months after a tooth extraction. The CBCT scan revealed remnants of a tooth root (radix) perforating into the right maxillary sinus, surrounded by a radiopaque intermediate area. Sinus perforation is a known occurrence in dentistry, and it requires thorough diagnostic imaging for proper evaluation. The tooth root remnants are typically located in the premolar and molar regions, near the base or medial wall of the sinus. The size of the tooth fragments within the sinus can be precisely measured, and the relationship of the remaining fragments to the maxillary sinus anatomy can be clearly defined. This detailed information enables clinicians to assess the extent of the lesion and its impact on surrounding structures, allowing for the development of an appropriate treatment plan for the patient. Conclusion: CBCT is a very adequate modality for supporting the examination of cases of residual tooth roots perforated to the sinuses because it can provide detailed information about the position, size, and relationship with the surrounding anatomy.